Nitrogen-doped hollow carbon nanoflowers from a preformed covalent triazine framework for metal-free bifunctional electrocatalysis. Issue 27 (2nd July 2020) - Zheng, Yong; Chen, Shan; Song, Hui; Guo, Hele; Zhang, Kai A. I.; Zhang, Chao; Liu, Tianxi
Abstract : N-doped hollow carbon nanoflowers with high nitrogen content up to 5.3 at% were prepared via a step-wise polymerization and carbonization route from a covalent triazine framework. Abstract : Fabrication of nitrogen-doped hollow carbon nanostructures is of great importance for achieving efficient electron and ion transport as a metal-free electrocatalyst. Herein, we report a step-wise polymerization and carbonization route to prepare N-doped hollow carbon nanoflowers (N-HCNFs) with a high nitrogen content up to 5.3 at%. A preformed covalent triazine framework (CTF) network assembled on a melamine-cyanuric acid (MCA) supermolecular crystal was achieved via a step-wise polymerization. The subsequent carbonization was conducted to obtain hollow and porous carbon materials with a unique flower-shape. Excellent electrochemical oxygen reduction reaction (ORR) performance with a positive half-wave potential of 0.84 V ( vs. RHE) was achieved with excellent stability and methanol resistance in alkaline media. Furthermore, for the hydrogen evolution reaction (HER), a low overpotential of 243 mV at a current density of 10 mA cm −2 and a small Tafel slope of 111 mV dec −1 in acidic media were shown.